Transparansi Sustainability Report: Kesehatan Keuangan, Lingkungan, dan Tata Kelola Perusahaan - Callista Donna Azaria; Shinta Permata Sari (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
Sustainability reporting has impact on increasing efficiency, cost efficiency and competitive advantage. This study assesses the effect of profitability, liquidity, leverage, carbon performance, and board independence on sustainability report disclosure in primary consumer sector companies listed on the Indonesia Stock Exchange from 2022 to 2024. A quantitative approach uses with secondary data from companies' annual reports and sustainability reports, which are analysed using multiple linear regression. 120 companies that made up the population, purposive sampling is used to obtain 40 companies that met the criteria to be sampled over an observation period of 3 years. The results of the study show that profitability, carbon performance, and board of board independence do not have an effect on sustainability report disclosure, while liquidity and leverage have no effect on sustainability report disclosure. These findings indicate that the financing structure of companies, as reflected in liquidity and leverage, encourages corporate transparency, while profit efficiency, environmental performance, and independent governance are not yet major factors.